Clinical preferences and trends of anti‐vascular endothelial growth factor treatments for diabetic macular edema in Japan. Issue 2 (26th October 2018) - Sugimoto, Masahiko; Tsukitome, Hideyuki; Okamoto, Fumiki; Oshika, Tetsuro; Ueda, Tetsuo; Niki, Masanori; Mitamura, Yoshinori; Ishikawa, Hiroto; Gomi, Fumi; Kitano, Shigehiko; Noma, Hidetaka; Shimura, Masahiko; et al.
Abstract: Aims/Introduction: To determine the current clinical preferences of anti‐vascular endothelial growth factor (VEGF) treatment protocols for diabetic macular edema (DME) in Japan. Materials and Methods: This was a descriptive cross‐sectional study. Answers to a questionnaire consisting of 16 questions were obtained from 176 of 278 (63.3%) surveyed ophthalmologists. Results: The results showed that 81.2% preferred intravitreal injections of anti‐VEGF antibodies as the first‐line therapy. The most important indicators for beginning anti‐VEGF therapy were: the best‐corrected visual acuity in 44.3% and the retinal thickness in 30.7%. In the loading phase, 53.4% preferred a single injection, and in the maintenance phase, 75.0% preferred the pro re nata regimen. Financial limitation (85.8%) was reported as the most important difficulty in the treatment. For combination therapy with anti‐VEGF treatment, panretinal photocoagulation, focal photocoagulations and a sub‐Tenon steroid injection were preferred. The contraindications for anti‐VEGF therapy were: prior cerebral infarction (72.7%). Regarding the use of both approved anti‐VEGF agents in Japan, ranibizumab and aflibercept, 39.8% doctors used them appropriately. Conclusions: Our results present the current clinical preferences of anti‐VEGF treatment for DME in Japan. The best‐corrected visual acuity and the retinal thickness are important indicators to institute this therapy. The majority of the ophthalmologists use anti‐VEGF treatment as first‐line therapy and prefer the 1 +  pro re nata regimen. Abstract : We show the current clinical preferences of anti‐VEGF)treatments for DME in Japan.